Clinical Characteristics and Outcomes of Patients With Primary Mediastinal Germ Cell Tumors: A Single-Center Experience - Wang, Lu; Zhao, Jun; An, Tongtong; Wang, Yuyan; Zhuo, Minglei; Wu, Meina; Wang, Ziping; Li, Jianjie; Yang, Xue; Chen, Hanxiao; Zhong, Jia (Frontiers in Oncology, 2020)
Purpose Primary mediastinal germ cell tumors (PMGCTs) are rare. The natural history and optimal treatment strategies still need to be defined. The aim of the study was to summarize the clinical characteristics, treatment outcomes and prognostic factors of PMGCTs. Methods Twenty-four patients with PMGCTs who were treated from December 2008 to January 2019 were evaluated retrospectively. The Kaplan-Meier method and Cox regression analysis were used to evaluate factors associated with prognosis. Results The study population consisted of 23 male patients and 1 female patient. Five patients were diagnosed with seminoma and 19 patients were diagnosed with nonseminoma. The median follow-up time for all patients was 15.8 (3.9-114.5) months. The 5-year overall survival (OS) and progression free survival (PFS) rates for all patients were 65.2% and 44.3%. For nonseminoma and seminoma, the 5-year OS rates were 54.1% and 100% (P=0.093), respectively, and the 5-year PFS rates were 28.7% and 100%, respectively. (P=0.044). In patients with nonseminoma, first-line radiotherapy indicated superior OS and PFS (P=0.037 and P=0.027, respectively). The median survival time after recurrence was 4.3 months and the 1-year survival rate after recurrence was 23.4%. Conclusion These results indicated that in PMGCTs, the prognosis of seminoma is superior to that of nonseminoma. Radiotherapy may be an essential treatment in patients with nonseminoma. Patients with relapse have unfavorable prognosis.